Efektivitas Platelet Rich Plasma (PRP) Dalam Meningkatkan Reseptivitas Endometrium Dan Luaran Reproduksi Pasien Dengan Kegagalan Implantasi Berulang: Systematic Literature Review - Dhinar Mustika Natalia; Evi Fitriany; Dhika Juliana Sukmana; Redhita Rizki Shantania Putri (Jurnal Pharmacopoeia, 2026)
Recurrent implantation failure (RIF) is a major cause of in vitro fertilization (IVF) failure and remains a significant challenge in assisted reproductive technology. RIF is frequently associated with impaired endometrial receptivity, particularly in women with thin endometrium. Conventional treatments have shown inconsistent outcomes, highlighting the need for alternative therapeutic approaches. Platelet-rich plasma (PRP) has emerged as a potential strategy to improve endometrial quality and receptivity. This study aimed to systematically review the role of PRP in improving reproductive outcomes in patients with RIF. This study was conducted as a systematic literature review using PubMed, Dimensions, and European PMC databases. Article searches were performed using the keywords “Platelet Rich Plasma,” “Recurrent Implantation Failure,” and “Fertility Outcome” with boolean operators and MeSH terms. Randomized controlled trials and retrospective cohort studies published between 2015 and 2025 were included. Article screening was conducted using Zotero and Rayyan. From 108 articles, 16 studies met the inclusion criteria and were qualitatively analyzed. The findings indicate that intrauterine PRP administration in patients with RIF is associated with improvements in endometrial thickness, implantation rate, biochemical pregnancy, clinical pregnancy, and live birth rate compared to standard therapy. The most consistent benefits were observed in patients with thin endometrium (≤7 mm), while outcomes in patients with normal endometrial thickness varied across studies. PRP shows promise as a safe and effective adjuvant therapy to enhance endometrial receptivity and pregnancy outcomes in patients with RIF. Further well-designed randomized controlled trials with standardized PRP protocols are required to establish its clinical efficacy.